Overview of Sabang Class II Checkpoint Immigration Office Authority of Foreign Ship and Solution Effort - Al Hafizh Ibnu Qoyyim (Jurnal Ilmiah Kebijakan Hukum, 2022)
This study aims to examine the Immigration authority of a foreign ship which was delegated by the Police who were arrested on suspicion of narcotics crimes committed by its crews. The ship entered Indonesian territory with an emergency status in November 2019. The crews and the ship were handed over to Sabang Immigration Office. The crews of the ship were subject to Immigration Administrative Action by being placed in the Medan Immigration Detention Center. Meanwhile, the ship became the responsibility of the Sabang Immigration Office. What is the authority of the Immigration Office against foreign ships for alleged narcotics crimes and what are the efforts made by Sabang Immigration? The qualitative research methodology in this research used data collected from various sources. The results of this study are based on the laws and regulations in force in Indonesia. They include the Immigration regulations which explain that the Immigration Office does not have authority over the ship since it is not in the realm of Immigration investigation. The Immigration Office sought to resolve the ship's problem by actively working with relevant agencies and coordinating with the leadership for instructions and directions.